2023
DOI: 10.1007/s13659-023-00375-2
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effect and mechanism insight of purified Antarctic krill phospholipids against mice ulcerative colitis combined with bioinformatics

Abstract: Antarctic krill oil is functional oil and has a complex phospholipids composition that poses difficulties in elucidating its effect mechanism on ulcerative colitis (UC). The mechanism of UC action was studied by bioinformatics, and the therapeutic effect of Antarctic krill phospholipids (APL) on dextran sulfate sodium (DSS)-induced colitis mice was verified. GO functional enrichment analysis uncovered an enrichment of these genes in the regulation of cell–cell adhesion, membrane region, signaling receptor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Recently, with the improvement of gene sequencing platforms, bioinformatics analyses have been used to identify differentially expressed genes. It has been published a number of reports on the use of arrays and chips for UC bioinformatics analysis (Shi et al 2020a ; Zhang et al 2020 ; Huang et al 2023 ), but the actual analysis for UC is still relatively little. As a result, bioinformatics techniques could improve our ability to investigate and comprehend UC’s underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the improvement of gene sequencing platforms, bioinformatics analyses have been used to identify differentially expressed genes. It has been published a number of reports on the use of arrays and chips for UC bioinformatics analysis (Shi et al 2020a ; Zhang et al 2020 ; Huang et al 2023 ), but the actual analysis for UC is still relatively little. As a result, bioinformatics techniques could improve our ability to investigate and comprehend UC’s underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that “krill” was mistakenly written as “kill” in the title.…”
mentioning
confidence: 99%